Mediating effects of attention problems on the link between parenting style and internet gaming disorder in adolescents - Chung, Sung Ah; Bae, Sujin; Kim, Hee Jin; Lee, Jea Woog; Hwang, Hyunchan; Han, Doug Hyun (Frontiers in Psychiatry, 2023)
Positive and negative parenting styles as well as psychiatric comorbidities including attention deficit hyperactivity disorder (ADHD) have been associated with internet gaming disorder (IGD) in children and adolescents. We hypothesized that ADHD and parenting style would be associated with IGD in adolescents. In addition, psychological status could mediate the link between parenting style and the severity of IGD.A total of 256 adolescents with IGD and 211 healthy internet game players and their mothers participated in the current study. Demographic data, gaming patterns, and psychological status including ADHD were recorded for all adolescents. The parenting style of each adolescent's mother was assessed using the Maternal Behavior Research Instrument (Korean version).There were significant differences in the internet game play patterns, psychological status, and parenting styles between the IGD group and healthy internet game players. In the hierarchical logistic regression analysis, higher ADHD scores, less affective parenting styles, and less autonomous parenting styles, were significant predictors of IGD. In the mediation test, the ADHD score was found to mediate the association between affective and autonomous parenting styles and the severity of IGD.Attention problems could directly and indirectly mediate the relationship between positive parenting styles and the severity of IGD. Our findings have the potential to aid in the development of treatment plans for IGD and ADHD as well as to contribute to the development of educational resources regarding parenting styles.